First record, current status, symptoms, infested cultivars and potential impact of the blueberry bud mite, Acalitus vaccinii (Keifer) (Prostigmata: Eriophyidae) in South Africa - (:unkn) unknown (My University, 2018)
Acalitus vaccinii (Keifer, 1939) is reported for the first time in South Africa, on cultivated blueberries (Ericaceae: Vaccinium spp.). This is the first known occurrence outside its likely native range in North America where it is a pest on cultivated and wild blueberries. In South Africa it has first been identified in 2014 and now occurs between Amsterdam and Lothair, and near Lydenburg and Dullstroom in the Mpumalanga Province. The morphology of the South African A. vaccinii specimens was compared with previous published taxonomic descriptions and differences were found. Infestation levels in South Africa were high, and reduced flower and berry formation considerably on various Vaccinium corymbosum L. cultivars, and on rabbiteye blueberry Vaccinium virgatum Aiton. \'Centurion\'. The current status of, symptoms, and cultivars infested by the mite in South African blueberry plantings are presented and discussed in the context of published information in North America. Acalitus vaccinii is a potential threat to cultivated blueberries in South Africa, but the threat varies according to climate and the susceptibility of different cultivars to this mite. Acalitus vaccinii will unlikely infest South Africa’s indigenous vegetation, apart from possibly the native Vaccinium exul Bolus.
Keywords: African Research